FIELD EVALUATION OF HOUSE FLY DELTA TRAPS IN PIGGERY AND CATTLE FARMS - S.T. Bino Sundar; T.J. Harikrishnan; Bhaskaran Ravi Latha; T.M.A. Senthil Kumar; G. Sarath Chandra; Serma Saravana Pandian; C. Pandian; K. Ambasankar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
In the present study, red acrylic delta traps were fabricated and evaluated in piggery and cattle farms to trap house flies. Two different pellet baits; one containing (Z)-9-Tricosene, fish meal and molasses (FMP) and other with added antioxidant, butylated hydroxy toluene (FMPB) were used in the traps. In piggery and cattle farms, the traps were suspended at a height of six feet from ground level using metal wires at a distance of three meters between each trap. Each trial was conducted for seven days and the trial was repeated six times continuously without replacement of baits. Trapped flies were counted after each trial. In piggery farm, a total of 1232 flies were trapped, out of which 454 and 778 flies were trapped in FMP and FMPB pellet baited traps, respectively. Total number of flies trapped in the first, second, third, fourth, fifth and sixth week of the study period was 308, 247, 196, 133, 204 and 144, respectively. In cattle farm, a total of 435 flies were trapped, out of which 160 flies were trapped in FMP pellet baited traps and remaining 63.21 per cent (275 flies) were trapped in FMPB pellet baited traps. Total number of flies trapped in the first, second, third, fourth, fifth and sixth week of the study period was 134, 96, 82, 55, 27 and 41, respectively. The variation in trap catches of flies in traps baited with FMP and FMPB pellets was highly significant in both piggery (χ2 value = 170.42** p<0.01) and cattle farms (χ2 value 60.80** p<0.01). Delta traps were found effective in luring house flies and can be used in livestock farms to control house flies.